Rekomendasi Wisata Umbul dengan K-Means Clustering - Fajar Pamungkas; Didik Nugroho; Yustina Retno Wahyu Utami (STMIK Sinar Nusantara, 2020)
District Klaten has many springs that are used by people for many things; one of them used for tourist attractions is umbul tourism. It is difficult to use K-Means Clustering Method for determine umbul tourism according to classification and spread in district Klaten. K-Means Clustering is a method of grouping data by taking parameters of a number clusters, and partitioning data into clusters, based on similarities between data in one cluster and dissimilarities between different clusters, the center of the cluster is the average of the cluster member values it called as centroid. The results of this study are grouping the umbul truism which are divided into three clusters namely Enough, Good and The Best. The result of the data, there are 4 umbul tourisms in the first cluster is Beautiful category, namely Tirtomoyo, Buto, Pancuran, and Besuki. In the third cluster of umbul tourism has good category, namely Tirto Mulyani umbul, Gedaren, Sumber Nila, Manten, Sigedang, and Kajen. In the best category in the second cluster has 8 umbul tourisms, namely Nila umbul, Tirto Mulyono, Ingas, Lumban Tirto, Ponggok, Tirto Raharjo, Jolotundo, and Tirtomulyono.Keywords: K-Means Clustering, Umbul, Umbul Category, Tourist Destination